Climate Change Adaptation and Human Resource Management: Examining Workforce Resilience across Geographically Vulnerable Regions (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Climate change stands out as one of the greatest global challenges facing organizations, employees, and labor markets in regions already vulnerable to environmental shifts. More frequent extreme weather like heat waves, floods, droughts, cyclones, and other climate threats throws business operations, workforce productivity, employee health, and long-term organizational stability into turmoil. Governments and companies have started to embrace climate adaptation measures, but fewer have really recognized how Human Resource Management (HRM) can play a strategic role in boosting workforce resilience to climate risks. This paper looks at ways to weave climate change adaptation into HRM practices so organizations in vulnerable areas can strengthen their workforce’s ability to adapt. By drawing on Dynamic Capabilities Theory, Organizational Resilience Theory, Human Capital Theory, and the Ability–Motivation–Opportunity (AMO) framework, the study builds a strong conceptual foundation for climate-responsive HRM. The research involves a systematic review of recent literature from 2015 to 2025, using peer-reviewed articles pulled from databases like Scopus, Web of Science, and ScienceDirect. This review highlights adaptive HRM strategies like climate-aware workforce planning, occupational health and safety measures, flexible work policies, ongoing employee training, psychological support, digital workforce management, and leadership training as essential drivers of organizational resilience. The results show that organizations in climate-vulnerable zones boost employee adaptability, cut down on disruptions, reinforce organizational commitment, and keep productivity high when they integrate climate adaptation into HR policies and strategic planning. This paper adds to the conversation on sustainable HRM by offering a framework that links climate adaptation actions with workforce resilience and organizational durability. It also lays out clear recommendations for managers and policymakers who want to build organizations that can weather future climate surprises.